Canadian recommendations for vitamin D intake for persons affected by multiple sclerosis. Issue 199 (May 2020) - Atkinson, Stephanie A.; Fleet, James C.
Highlights: Low Vitamin D status may contribute to increased MS disease risk. Evidence for vitamin D intake levels to prevent MS is not available. Evidence for vitamin D intake levels that alter MS disease course is not available. Guidelines for vitamin D intake and status in MS are the same as for healthy people. Abstract: In 2016, the Multiple Sclerosis (MS) Society of Canada convened a panel of expert scientists, clinicians and patient advocate to review the evidence for an association between vitamin D status and MS prevention and/or disease modification. The goal was to develop clear and accurate recommendations on optimal vitamin D intake and status for people affected by MS for use in clinical practice and public health policy. The final consensus report was based on a review and grading of existing published papers combined with expert opinions of panel members. The report led to recommendations published in November of 2018 on the website of the MS Society of Canada, one in a format for use by health professionals and another in a question and answer format that was targeted to persons affected by MS and the general public. For people at risk of developing MS, the vitamin D recommendations are similar to those for the general public following the Dietary Reference Intakes (DRI) for Canada and the United States. Adults should achieve and maintain a normal vitamin D status with monitoring by physicians (serum 25-hydroxyvitamin D (25(OH)D) = 50−125 nmol/L, requiring 600–4000 IU vitamin D/d intake). For pregnant women, newborn infants, and all youth at risk of MS, vitamin D intakes should also follow DRI recommendations but additionally their serum 25-(OH)D should be monitored. For persons living with MS, existing evidence did not allow prediction of a vitamin D intake that might modify MS disease course. For this group the recommendations included: (1) serum 25-(OH)D should be maintained in the range of 50–125 nmol/L (600–4000 IU/d intake).; and (2) vitamin D should not be used as a standalone treatment for MS. For children and adolescents, serum 25OHD status was recommended to be measured upon diagnosis of a first clinical demyelinating event, and monitored every 6 months to achieve a target of 75 nmol/L Since people living with MS are at increased risk of osteoporosis, falls, and bone fractures, it was recommended to achieve a minimum serum 25OHD concentration that is protective for bone health in the general population. The revision of the MS Society recommendations on vitamin D awaits future clinical trial evidence.